Capital Markets Union: The Key to Restoring the Economic Growth and the Real Convergence in the Eurozone - Rusek, Antonin (Archives of Business Research, 2015)
In the next decade or so the EU will face complete set of challenges. To confront successfully these challenges, the restoration of growth is the imperative. That means to restore the competitiveness especially on the Mediterranean littoral and hopefully the real convergence. Renewal of the North to South capital flows is the sine qua non of this development. The main tool in this endeavor is the emerging capital markets union, which will facilitate the increased activities of the venture capital – the main tool to create the new economy of innovation and creativity. But to be successful the capital markets union has to be complemented by reforms of labor markets, business creation environment and taxation. New approaches like special “economic innovation and growth” zones may be necessary. To fully implement the necessary structural reforms the cooperation of the private and public sector on both the EU and national levels is necessary.